Implications of cognitive abilities in students’ performance in physics using group dynamics and visual-clue strategies - Achor, Emmanuel E.; Ngbea, Philip M. (Univeritas Papua, 2022)
The study examined the implications of cognitive abilities of students on their academic performance when taught Physics using group dynamics and visual clue strategies. The quasi-experimental research design was adopted. The study population was 1,920 SSII students from 48 Secondary Schools in Makurdi metropolis from where the sample of 157 was drawn. The instruments: Physics Students’ Performance Test (PSPT) and Students’ Cognitive Ability Test (SCAT) were used for data collection. Hypotheses were tested at 0.05 level using Analysis of Covariance (ANCOVA). There was significant difference between the mean academic performance of students taught Physics using group dynamics strategy, visual strategy and demonstration method; there was significant difference among the mean abilities of students when group dynamics strategy was used and also when visual clue strategy was used in teaching Physics; there is significant difference between the interaction effect of strategies and cognitive abilities on academic performance of students in Physics. The study recommended among others that since the interaction effect of strategies and cognitive abilities on academic performance of students in Physics was significant, the use of both strategies could be useful in fostering the academic performance of students of high ability groups while use with low and moderate ability groups should be with caution